Community based maternal and child health nutrition project, Uttar Pradesh: An innovative strategy focusing on "At risk" families - Sheila C Vir (Wolters Kluwer Medknow Publications, 2013)
Research Question: Use of community based volunteers, frequently reaching and counseling a selected group of prioritized families, can make a substantial difference in improving maternal and child care practices and in reducing child undernutrition. Setting: Program Rural Uttar Pradesh, India. Study Design : A comparison of baseline and endline surveys following 4 years of community based project intervention Participants: "At risk" undernutrition families comprising mothers of under twos, newlyweds, and severely undernourished children below 6 years. Intervention: Mapping and counseling of "at risk" families. Measuring impact on maternal-child care practices, underweight status. Results: Trained community mobilizers identified and counseled selected "at risk" families. Following 4 years of implementation in 907 villages of 8 blocks of four districts, significant improvement was noted in practices of early initiation of breastfeeding, feeding colostrum, timely introduction of complementary feeding, and washing the hands after defecation. Percentage of mothers exclusively breastfeeding at 6 months was only 2.1% with 78% receiving prelacteal feeds. A small increase in normal and mild malnutrition and a significant reduction of 43% in severe malnutrition was noted. Conclusion: Frequently counseling by accredited social health activists by focusing on selected defined "at risk" families of under twos and those with severe malnourished children could result in increasing acceptability of correct child health, feeding, and care practices and in contributing to improving nutritional status scenario.